2002
DOI: 10.1016/s1010-7940(02)00246-4
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine therapy for patients at risk of renal dysfunction following cardiac surgery: science or fiction?

Abstract: Renal-dose dopamine therapy failed to offer additional renoprotection to patients considered at increased risk of renal dysfunction after CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 22 publications
0
39
0
3
Order By: Relevance
“…Dopamine Agonists. Despite the known ability of dopamine to increase renal blood flow at low doses, multiple studies of dopamine in cardiac and noncardiac surgical populations have failed to show a benefit in terms of either mortality or renal function (195)(196)(197)(198). Fenoldopam, a selective DA 1 agonist, has showed some promise in small studies (not all of them randomized) (199)(200)(201)(202), although this has not been universal (203).…”
Section: Current and Future Pharmacologic Strategiesmentioning
confidence: 99%
“…Dopamine Agonists. Despite the known ability of dopamine to increase renal blood flow at low doses, multiple studies of dopamine in cardiac and noncardiac surgical populations have failed to show a benefit in terms of either mortality or renal function (195)(196)(197)(198). Fenoldopam, a selective DA 1 agonist, has showed some promise in small studies (not all of them randomized) (199)(200)(201)(202), although this has not been universal (203).…”
Section: Current and Future Pharmacologic Strategiesmentioning
confidence: 99%
“…Th e preventive eff ect has, however, been questioned [19][20][21]. A prospective, random ized controlled trial showed that low-dose dopamine did not aff ect renal outcome in septic patients with early AKI [22].…”
Section: Eff Ects Of Dopaminergic Agents On Renal Oxygenation In the mentioning
confidence: 99%
“…However, it had also been reported that, when compared with the untreated group, dopamine increased urinary volume but worsened tubular disorders at an early stage and the renal protective effects of dopamine were not verified. [23][24][25][26] In a study on cardiac surgery patients with normal renal function divided into furosemide, dopamine, and untreated groups, the sCr increase rate was significantly higher in the furosemide group than in the other two groups. Creatinine clearance was significantly lower and none of the patients in the other two groups required hemodialysis, but the sCr increase was 4.9% in the furosemide group.…”
Section: Discussionmentioning
confidence: 99%
“…In the dopamine group, the rate of sCr increase was low when compared with the furosemide group but no difference from the untreated group was reported. 23) Furosemide increased the urinary volume because of its potent natriuretic action, but increases in sCr, decreases in eGFR, exacerbation of the RAAS and conversely, aggravated renal dysfunction has also been reported. 20,23,27,28) In the present research, strong natriuresis was observed in the placebo group.…”
Section: Discussionmentioning
confidence: 99%